Problem Based Learning Oriented Thematic Worksheets: Increased Discipline of Elementary School Students - Nugraheni, Wahyu Nur; Sutama (LPPM Undiksha, 2023)
Learning activities in elementary schools are carried out by paying attention to all aspects that need to be nurtured and developed properly. Learning activities must cover three domains, namely affective, cognitive, and psychomotor. The teacher's patterns and strategies in implementing the concept understanding process are important points in delivering learning. Worksheets is certainly a process for students to seek further understanding of the concepts presented by the teacher. This study aims to analyze the effect of problem-based learning-oriented thematic worksheets on discipline character of elementary school students. This research method is quasi-experimental on the fourth grade students. The data analysis applied, namely the t-test, is one of the parametric statistical tests with two measurements. In implementing the problem-based learning-oriented thematic worksheets, there are several stages, namely introduction to the teacher, pre-test implementation, introduction to students, post-test implementation, and processing data with validity and reliability tests. By getting the results the average pre test shows 3.125 and the average post test shows 3.575. From these results, there is an increase in discipline in working on worksheets.